Cheating at Ethics: - Baranek, Devon; Dunne, Kathleen (STIE Malangkucecwara, 2025)
This teaching case utilizes a real-world example of ethics violations occurring at Ernst and Young, one of the Big Four accounting firms. An SEC investigation revealed widespread cheating by its employees on professional education exams required for CPA licensing. The misconduct violated federal securities laws and the codes of conduct of several professional organizations. It was also not the first time EY had addressed ethical misconduct amongst its employees, but it failed to prevent or stop the practice from continuing. EY was fined 100 million and required to hire independent consultants to review its policies, ethics and disclosure procedures. Students are required to read through the case and work in groups to answer questions ranging in difficulty based on course level. The EY case is simple enough to be understood by all students, but may be used as a starting point for more advanced discussions on the ethical obligations and responsibilities of accountants and the accounting profession.